Enhancing Pancasila Student Profiles Through Differentiated Learning with Understanding by Design - Rokhmaniyah Rokhmaniyah; Dewi Indrapangastuti; Muhamad Chamdani (STAI Hubbulwathan Duri, 2025)
Education in Indonesia has yet to fully accommodate the diverse interests, talents, and abilities of students, limiting the development of their creativity and character. This study aims to (1) examine the effectiveness of differentiated learning using the Understanding by Design (UbD) framework in enhancing aspects of the Pancasila Student Profile, and (2) explore student responses to this instructional approach. The research employed a mixed-methods design, specifically a sequential exploratory strategy, combining qualitative and quantitative data. The quantitative component followed a quasi-experimental design with a non-equivalent control group using a pretest-posttest format. Data were gathered through observations, interviews, tests, and questionnaires. The findings indicate a significant improvement in the Pancasila Student Profile in the treatment group after the implementation of UbD-based differentiated instruction. The normalized gain score (N-Gain) was 0.82, categorized as high, while the effect size (Cohen’s d) was 0.49, indicating a moderate impact. Additionally, student responses measured via Likert-scale questionnaires showed a very strong positive perception of the learning experience, particularly in aspects of engagement, relevance, and collaboration. These results suggest that differentiated instruction designed through the UbD framework is effective in promoting the core competencies of the Pancasila Student Profile—independence, mutual cooperation, and critical thinking. This approach provides a practical pathway for educators to implement learner-centered instruction aligned with the goals of the Kurikulum Merdeka, fostering both academic and character development among elementary students.